First-line sunitinib versus pazopanib in metastatic renal cell carcinoma: Results from the International Metastatic Renal Cell Carcinoma Database Consortium. (September 2016) - Ruiz-Morales, Jose Manuel; Swierkowski, Marcin; Wells, J. Connor; Fraccon, Anna Paola; Pasini, Felice; Donskov, Frede; Bjarnason, Georg A.; Lee, Jae-Lyun; Sim, Hao-Wen; Sliwczynsk, Andrzej; Ptak-Chmielewska, Aneta; Teter, Zbigniew; et al.
Abstract: Background: Sunitinib (SU) and pazopanib (PZ) are standards of care for first-line treatment of metastatic renal cell carcinoma (mRCC). However, how the efficacy of these drugs translates into effectiveness on a population-based level is unknown. Patients and methods: We used the International mRCC Database Consortium (IMDC) to assess overall survival (OS), progression-free survival (PFS), response rate (RR) and performed proportional hazard regression adjusting for IMDC prognostic groups. Second-line OS (OS2) and second-line PFS (PFS2) were also evaluated. Results: We obtained data from 7438 patients with mRCC treated with either first-line SU (n = 6519) or PZ (n = 919) with an overall median follow-up of 40.4 months (95% confidence interval [CI] 39.2–42.1). There were no significant differences in IMDC prognostic groups (p = 0.36). There was no OS difference between SU and PZ (22.3 versus 22.6 months, respectively, p = 0.65). When adjusted for IMDC criteria, the hazard ratio (HR) of death for PZ versus SU was 1.03 (95% CI 0.92–1.17, p = 0.58). There was no PFS difference between SU and PZ (8.4 versus 8.3 months, respectively, p = 0.17). When adjusted for IMDC criteria, the HR for PFS for PZ versus SU was 1.08 (95% CI 0.981–1.19, p = 0.12). There was no difference in RR between SU and PZ (30% versus 28%, respectively, p = 0.15). We also found no difference in any second-line treatment between either post-SU or post-PZ groups for OS2 (13.1 versus 11 months, p = 0.27) and PFS2 (3.7 versus 5.0 months, p = 0.07). Conclusions: We confirmed in real-world practice that SU and PZ have similar efficacy in the first-line setting for mRCC and do not affect outcomes with subsequent second-line treatment. Highlights: Sunitinib and pazopanib have similar efficacy for metastatic renal cell carcinoma. Use of either one does not affect subsequent second-line outcomes. Second-line decisions should be made based on individualisation of patient needs.